2011
DOI: 10.1111/j.1742-4658.2011.08267.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between the N‐terminal and C‐terminal domains of Mycobacterium tuberculosis HupB is essential for high‐affinity binding, DNA supercoiling and inhibition of RecA‐promoted strand exchange

Abstract: The occurrence of DNA architectural proteins containing two functional domains derived from two different architectural proteins is an interesting emerging research theme in the field of nucleoid structure and function. Mycobacterium tuberculosis HupB, unlike Escherichia coli HU, is a two-domain protein that, in the N-terminal region, shows broad sequence homology with bacterial HU. The long C-terminal extension, on the other hand, contains seven PAKK/KAAK motifs, which are characteristic of the histone H1/H5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 74 publications
(140 reference statements)
4
28
1
1
Order By: Relevance
“…Previously, the N-terminal domain (1 to 95 aa) has been shown to interact with DNA, albeit at a lower efficiency compared to the full-length HupB, leading to speculation that the C-terminal domain acts as a DNA clasp (43). We, however, observed that the N-terminal domain (1 to 108 aa) used in the present study demonstrated a higher affinity to dsDNA compared to a shorter fragment of the N-terminal domain (1 to 95 aa) used previously (42). This could partially be attributed to the length of the N-terminal domain and shows that the residues beyond the HU fold may be critical for N-HupB-DNA interaction.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Previously, the N-terminal domain (1 to 95 aa) has been shown to interact with DNA, albeit at a lower efficiency compared to the full-length HupB, leading to speculation that the C-terminal domain acts as a DNA clasp (43). We, however, observed that the N-terminal domain (1 to 108 aa) used in the present study demonstrated a higher affinity to dsDNA compared to a shorter fragment of the N-terminal domain (1 to 95 aa) used previously (42). This could partially be attributed to the length of the N-terminal domain and shows that the residues beyond the HU fold may be critical for N-HupB-DNA interaction.…”
Section: Discussioncontrasting
confidence: 55%
“…6A. GST-N-HupB showed efficient interaction with double-stranded DNA (dsDNA) and with a higher affinity than previously reported (42). The promoter region of the Rv1230c gene, another member of CRP regulon, also displayed a similar binding affinity with HupB (data not shown).…”
Section: Fig 2 Endogenous Hupb Of M Tuberculosis H 37 Ra Is Phosphormentioning
confidence: 63%
See 1 more Smart Citation
“…Homologous NAPs are widely distributed across bacterial species, including Mycobacteria, Streptomyces, Rhodococcus, and Corynebacteria (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24); however, they are far less well characterized. The focus of the present study is mainly on the characterization of the IHF of M. tuberculosis; consequently, the existing literature relevant to IHF is discussed here.…”
mentioning
confidence: 99%
“…The N-and C-terminal extensions in HU resemble the (S/T)PKK repeats in the C-terminal domain of eukaryotic histone H1, which are involved in DNA compaction (Bharath et al, 2002). In vitro experiments have shown that the Mycobacterium HU extensions have an important contribution to DNA binding, modulate the DNA binding specificities compared with the corresponding truncated proteins consisting of the conserved core HU domain, and may have a role in DNA protection and compaction (Grove, 2011;Kumar et al, 2010;Mukherjee et al, 2008;Sharadamma et al, 2011). In vitro DNA-binding experiments have also been performed with recombinant D. radiodurans HU proteins (i.e.…”
Section: Introductionmentioning
confidence: 99%